Reputational Risk: A Bibliometric Review of Relevant Literature - Fayrouz Aksam Elsaied; Maryam Alhajjar; Ghada Abushairah; Safaa Al Harbi; Haitham Nobanee (Ital Publication, 2023)
This paper focuses on analyzing the level of research development regarding reputational risk on a general basis to identify what topics remain to be investigated. As a result, it offers a broader scope of research, including research debates, resolutions, and gaps that are relevant to the topic. A bibliometric analysis has been employed in this study to identify the topic’s trends and pinpoint potential gaps in the literature. The data were collected from the Scopus database for the period of 1994–2022, where the search resulted in a total of 659 documents relating in any way to reputational risk that fit the selection criteria. Research shows that conducted investigations are in favor of reputation risk and e-commerce, reputation insurance, corporate social responsibility, operational risk, risk management, and sustainability reporting. However, some of the articles' results on related topics were contradictory, and others found no evidence relating to reputation risk; some other topics were not fully examined or presented in the literature. Therefore, the current topic-related literature does not suffice, and further research is required to cover more topics on reputation risk and further highlight alignment between similar studies. This study has brought to light the relevant papers related to reputational risk and demonstrated potential gaps in the literature by investigating articles’ contradictory results on the researched topics, in turn conveying which topics need further examination. Thus, the literature will continue to evolve as members of the global academic community strive to fill the gaps and identify potential rescue strategies for jeopardized business entities. Doi: 10.28991/ESJ-2023-07-02-025 Full Text: PDF